Analysis of Nurses' Quality of Work Life at Ternate Hospital - Dramora Nepy Asmara; Kosasih; Yuliaty, Farida (Jurnal Manajemen Informasi Kesehatan (Health Information Management), 2025)
Nurses, as one of the human resources in hospitals, play a crucial role as a profession that constantly interacts with patients. Therefore, the performance of nurses, who play a crucial role in the hospital, is influenced by the quality of work life. Quality of work life is a state in which employees can fulfill their essential needs by working within the organization. The purpose of this study was to determine the quality of work life of nurses at Ternate Hospital. Data collection was conducted using a total sampling technique, with 80 nurses being the entire population. Data collection was conducted using a questionnaire. Data analysis used univariate analysis. The overall average score for quality of work life was 157.6 (SD = 11.41). The conclusion of this study is that the overall quality of work life and its individual dimensions are at a moderate level. Quality of work life is important for identifying capacity to meet the needs of society and the workplace.